Some New Variants of Hermite–Hadamard and Fejér-Type Inequalities for Godunova–Levin Preinvex Class of Interval-Valued Functions - Zareen A. Khan; Waqar Afzal; Waqas Nazeer; Joshua Kiddy K. Asamoah (Journal of Mathematics)
The theory of inequalities is greatly influenced by interval-valued concepts, and this contribution is explored from several perspectives and domains. The aim of this note is to develop several mathematical inequalities such as Hermite–Hadamard, Fejér, and the product version based on center radius CR-order relations. Furthermore, we develop several nontrivial examples and remarks to support the main findings.